Utilization of Artificial Intelligence (AI) in Indonesian Language Learning in Elementary Schools: Teacher Perceptions and Challenges - Agung Syah Putra; Dio Saputra (Universitas Muhammadiyah Lamongan, 2025)
The rapid expansion of Artificial Intelligence (AI) has begun to influence instructional practices in primary education, including Indonesian language learning. Although AI offers opportunities for automated feedback and personalized learning, existing studies in Indonesia have largely focused on AI use in general subjects or secondary and higher education levels, with limited empirical investigation into its application in primary-level Indonesian language instruction, particularly from the perspective of classroom teachers. Moreover, little is known about how teachers mediate AI use in relation to cultural and pedagogical appropriateness. Therefore, this study addresses this gap by exploring elementary school teachers’ perceptions and classroom experiences of AI integration in Indonesian language learning. This study aims to explore the perceptions and classroom experiences of Indonesian language teachers in utilizing AI for literacy learning in primary schools. A qualitative descriptive approach was used, involving twelve teachers selected through purposive sampling. Data were collected through semi-structured interviews, classroom observations, and document analysis. The findings show that teachers generally view AI as helpful in providing immediate corrective feedback, supporting instructional preparation, and increasing student engagement. However, challenges were also identified, including limited digital infrastructure, diverse teacher digital literacy, ethical concerns related to data security, and the risk of students relying too heavily on AI-generated suggestions. The study concluded that AI can make a meaningful contribution to Indonesian language learning when used under teacher supervision. Specifically, the results showed that teachers utilized AI to provide automatic corrections for spelling and structure, guide the process of developing open-ended sentence materials, and assist with task differentiation for students with varying abilities. Furthermore, it was found that teachers' limited digital literacy, limited availability of devices in schools, and a lack of formal training were key barriers to optimizing AI use. Therefore, educators play a mediating role to ensure that AI output remains pedagogically and culturally appropriate. Implications for policy development, teacher professional training, and future research are also discussed.